Artificial intelligence and data mining for mergers and acquisitions - Chanda, Debasis (Boca Raton : Chapman & Hall/CRC, 2018)
The goal of this book is to present a modeling framework for the Virtual Organization that is focused on process composition. This framework uses Predicate Calculus Knowledge Bases. Petri Net-based modeling is also discussed. In this context, a Data Mining model is proposed, using a fuzzy mathematical approach, aiming to discover knowledge. A Knowledge-Based framework has been proposed in order to present an all-inclusive knowledge store for static and dynamic properties. Toward this direction, a Knowledge Base is created, and inferences are arrived at. This book features an advisory tool for Mergers and Acquisitions of Organizations using the Fuzzy Data Mining Framework and highlights the novelty of a Knowledge-Based Service-Oriented Architecture approach and development of an Enterprise Architectural model using AI that serves a wide audience. Students of Strategic Management in business schools and postgraduate programs in technology institutes seeking application areas of AI and Data Mining, as well as business/technology professionals in organizations aiming to create value through Mergers and Acquisitions and elsewhere, will benefit from the reading of this book.
OCLC-licensed vendor bibliographic record.
Keywords: Consolidation and merger of corporations -- Computer networks; Consolidation and merger of corporations -- Mathematical models; Artificial intelligence; Data mining; BUSINESS & ECONOMICS / Management Science; COMPUTERS / General; COMPUTERS / Computer Graphics / Game Programming & Design